Continuous Prestress in Launched Extradosed Bridges - Van Bogaert, Philippe; De Backer, Hans (Frontiers in Built Environment, 2019)
The original concept of extradosed posttensioning in bridges is to obtain larger eccentricity of the tendons and thus to generate larger bending moments, opposing the external loading. This concept has been modified to constitute hybrid extradosed-cable supported bridges. However, the initial idea has the advantage to allow continuous prestressing, the number of costly anchors being minimized. On the basis of a set of geometrical equations and equalizing the live loads to a set of external forces, the conditions for concrete compression and tension are verified. In addition, the compliance with conditions for launching as a whole structure of extradosed bridges is examined. Some clarifying conclusions have been found, such as that extradosed prestress must be supplemented by additional centred prestress, an optimum deviator height can be derived and the amount of required prestress is a relatively stable fraction of the bridge girders. As the main span length increases, the extradosed prestress becomes more effective, although the auxiliary centred prestress takes the largest part in the total amount, thus confirming the character of this type of structures, which remains principally a prestressed concrete girder system The feasibility of launching as a whole has been demonstrated, provided the main span length does not exceed 60m.